Structure of Rap1b bound to talin reveals a pathway for triggering integrin activation. Issue 1 (December 2017) - Zhu, Liang; Yang, Jun; Bromberger, Thomas; Holly, Ashley; Lu, Fan; Liu, Huan; Sun, Kevin; Klapproth, Sarah; Hirbawi, Jamila; Byzova, Tatiana; Plow, Edward; Moser, Markus; et al.
Abstract Activation of transmembrane receptor integrin by talin is essential for inducing cell adhesion. However, the pathway that recruits talin to the membrane, which critically controls talin's action, remains elusive. Membrane-anchored mammalian small GTPase Rap1 is known to bind talin-F0 domain but the binding was shown to be weak and thus hardly studied. Here we show structurally that talin-F0 binds to human Rap1b like canonical Rap1 effectors despite little sequence homology, and disruption of the binding strongly impairs integrin activation, cell adhesion, and cell spreading. Furthermore, while being weak in conventional binary binding conditions, the Rap1b/talin interaction becomes strong upon attachment of activated Rap1b to vesicular membranes that mimic the agonist-induced microenvironment. These data identify a crucial Rap1-mediated membrane-targeting mechanism for talin to activate integrin. They further broadly caution the analyses of weak protein–protein interactions that may be pivotal for function but neglected in the absence of specific cellular microenvironments. The transmembrane receptor integrin is activated by talin, but so far it has remained elusive how talin is recruited to the plasma membrane. Here, the authors identify the Rap1-mediated membrane-targeting mechanism for talin, present the Rap1b/talin-F0 structure and show that talin is a direct Rap1b effector.